2016
DOI: 10.1186/s12967-016-0830-z
|View full text |Cite
|
Sign up to set email alerts
|

Phosphatase of regenerating liver 3 (PRL-3) is overexpressed in human prostate cancer tissue and promotes growth and migration

Abstract: BackgroundPRL-3 is a phosphatase implicated in oncogenesis in multiple cancers. In some cancers, notably carcinomas, PRL-3 is also associated with inferior prognosis and increased metastatic potential. In this study we investigated the expression of PRL-3 mRNA in fresh-frozen samples from patients undergoing radical prostatectomy because of prostate cancer (PC) and the biological function of PRL-3 in prostate cancer cells.MethodsSamples from 41 radical prostatectomy specimens (168 samples in total) divided int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 39 publications
1
31
0
Order By: Relevance
“…Similar to the cancers described above, upregulated PRL‐3 in tumors has been found in cervix , kidney , glioma , bladder , melanoma , lung , and prostate cancers. As for PRL‐1 and ‐2, using microarray analysis, mRNA levels were shown to be upregulated in pancreatic tumor samples compared with those of normal pancreas .…”
Section: Prl Expression In Tumors and Metastases: Emerging Biomarker supporting
confidence: 70%
See 1 more Smart Citation
“…Similar to the cancers described above, upregulated PRL‐3 in tumors has been found in cervix , kidney , glioma , bladder , melanoma , lung , and prostate cancers. As for PRL‐1 and ‐2, using microarray analysis, mRNA levels were shown to be upregulated in pancreatic tumor samples compared with those of normal pancreas .…”
Section: Prl Expression In Tumors and Metastases: Emerging Biomarker supporting
confidence: 70%
“…However, one study indicated that PRL-3 expression has no clinical role in ovarian carcinoma, whereas surprisingly PRL-1 and PRL-2 expression is associated with longer survival [113]. Similar to the cancers described above, upregulated PRL-3 in tumors has been found in cervix [114], kidney [115,116], glioma [117,118], bladder [119], melanoma [120], lung [121], and prostate [122][123][124] cancers. As for PRL-1 and -2, using microarray analysis, mRNA levels were shown to be upregulated in pancreatic tumor samples compared with those of normal pancreas [125].…”
Section: Prl Expression In Tumors and Metastases: Emerging Biomarker mentioning
confidence: 85%
“…Protein tyrosine phosphatase 4A3 (PTP4A3), also known as phosphatase of regenerating liver 3 (PRL-3), is an oncogenic phosphatase that has received significant attention as a potential therapeutic target in a variety of cancers 7,8,10 . PRL-3 is highly expressed in~80% of 151 human tumor tissue samples across 11 tumor types, including liver, lung, colon, breast, stomach, thyroid, pancreas, kidney, bladder, and prostate cancer 10 , and PRL-3 has been extensively reported as a biomarker of tumor progression and metastasis in breast 11 , colon 12,13 , gastric 14 , brain 15 , and prostate 16 cancers. Elevated PRL-3 correlates with reduced survival in patients with breast 17 , gastric 14 , ovarian 18 , and liver 19 cancers and in acute myelogenous leukemia (AML) 20,21 .…”
mentioning
confidence: 99%
“…While their normal cellular functions are largely unknown, the PRL family has been repeatedly shown to be involved in cancer progression. In particular, PRL-3 is a well-defined biomarker of metastasis in multiple cancer types, including melanoma, colorectal, and ovarian cancers, where PRL-3 expression is significantly higher in metastatic lesions compared to the primary tumor site [6][7][8][9][10][11][12][13][14] . In a comprehensive study of 151 patient samples across eleven common human tumors types, PRL-3 protein expression was upregulated in 80.6% of tumor samples compared to matched normal tissue 15 .…”
Section: Introductionmentioning
confidence: 99%